SIFAT LISTRIK MEMBRAN SELULOSA ASETAT - TITANIUM DIOKSIDA - Jajang Juansah (Jurnal Biofisika, 2012)
Membrane is a semiperiable tissue. Now days, the technology of membrane is commonly used for separation process. Research membrane filtration process is mostly done, but the investigations of their electrical properties are rarely performed. Electrical properties of membrane were investigated by using measurement of current-voltage, capacitance, and impedance phenomenon at low alternating current. The more value of frequency of signal, the more of conductance value. The capacitance and impedance were decreased If frequency was inclined. The TiO2 addition in cellulose membrane couse the electrical properties of membrane changes. It was happen until optimum value TiO2. The differences in electrical parameters was shaw clearly in the range of 10 Hz to 1 kHz.